Windfall income shocks with finite planning horizons - Michael Boutros (Bank of Canada, 2022)
How do households respond to unanticipated income shocks? I build and estimate a quantitative model of bounded rationality in which reoptimization is costly. Households respond to windfall income shocks by choosing a finite planning horizon over which to reoptimize. The optimal horizon is increasing in income, wealth, and the magnitude of the income shock. In the estimated model, the distribution of consumption responses is consistent with two motivating facts: highly liquid households have large consumption responses out of income shocks that cannot be driven by borrowing constraints, and larger income shocks induce smaller consumption responses.
Keywords: D91; E21; G51; 330; Economic models; Fiscal policy; Domestic demand and components